Capacity for information technologies and organizational performance: mediating effect of the absorption capacity - Guisao, Santiago (Pontificia Universidad Javeriana, 2018)
The aim of this paper is to analyze the mediating effect of Absorptive Capacity (AC) in the relationship between Information Technology Capabilities (ITC) and Organizational Performance, particularly financial performance (FP) and non-financial performance (NFP). The hypothesis model was tested on a sample of manufacturing and service companies, for which a structural equation by the least squares method was used. As for the results it was found that there is a total mediation of AC in the relationship between ITC and FP, and a partial one between ITC and NFP. In conclusion, to achieve the ITC impact on business results, its articulation is needed with soft organizational skills such as AC.